FORMAÇÃO INICIAL DE PROFESSORES DE INGLÊS PARA A EDUCAÇÃO INFANTIL EM CONTEXTOS BRASILEIROS: DIÁLOGOS POSSÍVEIS E DESEJÁVEIS - Galvao, Ana Sara Manhabusque (2022)
The offer of the English language in Early Childhood Education has becoming a reality in several Brazilian contexts. For this reason, the demand for specific teacher education for this field is also focused. This area is considered between language education (majors in English) and pedagogic education in the area of child development (Pedagogy courses), however, we understand that it is possible to overcome this dichotomy. Our proposal is to go beyond the disciplinary borders of the majors mentioned, searching for a transdisciplinary view on the context. The aim of this research was to analyze curricular proposals of majors of English Language and Literature in Brazilian Federal and State Universities, focused on the initial education of English teachers to work in Early Childhood Education. In this sense, after searching in the E-MEC website, 108 institutions were listed to be a part of this research. From those, 89 offered the major in English or Portuguese-English and, among them, 84 presented some document to continue the analysis. After the investigation, 15 universities presented approaches focused on reaching this expanding context. With the goal of also investigating local realities of universities, five institutions were invited to participate in an interview to clarify and expand points highlighted in their documents. Thus, through reflections based on curriculum theories, transdisciplinarity, teacher education and English language for children, we aim to offer a national overview and local aspects around English teacher education for this specific context. The results found present some possible dialogues. Furthermore, the strategies used by several Brazilian universities point out the possibilities of understanding English teacher education to work with children as a new space, closely related to the local context and marked by reflections, questioning and issues. We hope this research contributes to strengthen the studies in the field of English teacher education to work in Early Childhood Education.